THE EFFECT OF COMMUNITY LANGUAGE LEARNING MODEL ON STUDENTS’ SPEAKING ABILITY (A Study at the Tenth Grade of SMA Negeri 5 Padangsidimpuan 2018/2019 Academic Year) - RISWANDY HALOMOAN (JURNAL LINER (Language Intelligence and Educational Research), 2020)
Abstract:The aim of this research is to find out: 1) The application of community language learning model on students’ speaking ability, 2) The students’ speaking ability before and after using community language learning model, and 3) Whether there is a significant effect of community language learning model on students’ speaking ability. The population of this research is all the tenth grade, they are 248 students. The writer will use systematic sampling. The total sampling is 35 students. The writer uses experimental method. To collect the data, the writer uses observation and test. In analysis the result of the test, the researcher use ttest. After collecting the data, the result of this research are the application of community language learning model on students’ speaking ability is 3.6. It is categorized “Very Good”. The students’ speaking ability before community language learning model is 75.29. It is categorized “Good”. The students’ speaking after community language learning model is 84 It is categorized “Very Good”. The calculation of ttest formula is 7.15. The table score of ttable 5% significant level df it is 34, the result is 2.03. It is found that t0 calculation is bigger than ttable (7.15 > 2.03). It means that there is a significant effect of community language learning model on students’ speaking ability at the tenth grade of SMA Negeri 5 Padangsidimpuan. Keywords: Community Language Learning Model, Speaking